2021
DOI: 10.3390/ijerph182412981
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Sexual Orientation Microaggression with Anxiety and Depression among Lesbian, Gay, and Bisexual Taiwanese Youth: Self-Identity Disturbance Mediates but Gender Does Not Moderate the Relationships

Abstract: The aims of this cross-sectional survey study were to examine the association between sexual orientation microaggression and anxiety and depression among young adult lesbian, gay, and bisexual (LGB) individuals in Taiwan, as well as to examine the mediating effect of self-identity disturbance and the moderating effect of gender. In total, 1000 self-identified LGB individuals participated in the study. The experience of sexual orientation microaggression was assessed using the Sexual Orientation Microaggression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
2
10
0
1
Order By: Relevance
“…LGB individuals who experience these distal and proximal stressors can become hypervigilant because of the expectation of prejudicial events related to sexual orientation and can progressively develop rumination and psychopathology, such as depression ( 52 ). Consistently with the results of previous studies ( 22 24 ), the present study revealed significant associations of FSS and SOMs with depression in LGB individuals. These results support that intervention programs should be developed to reduce sexual stigma in the public, families, and LGB individuals and to prevent the development of depression among LGB individuals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…LGB individuals who experience these distal and proximal stressors can become hypervigilant because of the expectation of prejudicial events related to sexual orientation and can progressively develop rumination and psychopathology, such as depression ( 52 ). Consistently with the results of previous studies ( 22 24 ), the present study revealed significant associations of FSS and SOMs with depression in LGB individuals. These results support that intervention programs should be developed to reduce sexual stigma in the public, families, and LGB individuals and to prevent the development of depression among LGB individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Sexual orientation microaggressions (SOMs) are a more subtle and covert daily demonstration of sexual stigma toward LGB individuals and their sexual orientation than public sexual stigma ( 21 ). FSS, ISS, and SOMs are all psychological stressors for LGB individuals ( 4 ) and can compromise their mental health ( 22 24 ). A study discovered that being victimized by enacted sexual stigma significantly increased the risk of developing PIU ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also reported that gay and bisexual men who experienced victimization of homophobic bullying during childhood have self-identity disturbances in emerging adulthood [ 46 ]. Moreover, self-identity disturbance mediates the association between microaggression due to sexual orientation and mental health problems among young adult LGB individuals [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gay and bisexual men are still seen as the symbol of disseminating human immunodeficiency virus infection and deteriorating traditional family values [46]. Victimization of homophobic bullying [47,48], public stigma [49], microaggression [50,51], and internalized stigma [52] are prevalent among LGB individuals. Especially, the groups opposing same-sex marriage in Taiwan spread a considerable amount of incorrect information and rumors to malign LGB individuals through social media and public media; these misleading portrayals and negative stereotypes spread in the media demoralized LGB individuals and directly disturbed their emotional regulation [53][54][55][56][57][58].…”
Section: Mental Health Among Lgb Individuals In Taiwanmentioning
confidence: 99%